CAREER SATISFACTION AND PSYCHOLOGICAL WELL-BEING AMONG PROFESSIONAL ENGINEERS IN MALAYSIA: THE EFFECT OF CAREER GOAL DEVELOPMENT - Norizan Baba Rahim; Siti-Rohaida, M. Z. (Asian Academy of Management Journal, 2015)
As fast-track individuals who have special knowledge and expertise, engineers have great expectations and ambitions for their career. They are known to striving for their psychological success as well as being energetic in climbing their career ladder. Nevertheless, several factors such as conflict between having their own goals and expectation with advancement opportunities, work autonomy, and work demand structured by their organization, have influenced the well-being of the engineers. Consequently, engineers are found to be one group of unhappy workers in Malaysia. This scenario would become worse if little attention is given to research on the engineer’s individual well-being. Thus, it is timely to conduct a study to assess the level of individual well-being among Malaysian engineers, with career goal development as a predictor. This study applied self-administered questionnaire for collecting data. A total of 500 questions were distributed to registered professional engineers with 387 returned for analysis. The measures used were adopted from various previous studies with acceptable reliabilities. The hypotheses were investigated through correlation and path analysis using PLS. The research findings have provided useful information on the positive influence of protean career orientation on psychological well-being. Furthermore, the results showed that career goal development has a positive influence on individual well-being. The implications of these findings to the understanding of the process through career attitude affects individual well-being will be discussed.